(untitled) (Bangladesh Journal of Medical Education, 2023)
This cross sectional study was conducted to evaluate the MBBS (Bachelor of Medicine and Bachelor of Surgery) course of Bangladesh on the basis of modern ‘Integrated teaching’ instead of corresponding traditional ‘Discipline-based teaching’. The study was conducted during the period of January 2021 to December 2021. Data were collected from conveniently selected eight medical colleges of Bangladesh. One self-administered semi-structured questionnaire was administered to collect data from 87 teachers and from 413 students of MBBS course. It was found that out of 4 point scale (1 to 4) the mean scores of respondents’ views regarding ‘Integrated teaching’ in the present curriculum was 1.2; on the other hand, their views regarding the future MBBBS course should adopt ‘Integrated teaching’ instead of traditional ‘Discipline based teaching’ was 3.47. The score of the respondents’ opinion regarding the different requirements were above 3.4 out of 4. Now it is best time to shift our MBBS course towards ‘Integrated teaching’ in instead of ‘Discipline-based teaching’. Bangladesh Journal of Medical Education Vol.14(1) January 2023: 56-62